Representações sociais de crianças sobre Cuiabá antes e depois da Copa do Mundo 2014 - Cunha, Jeysson Ricardo Fernandes da (2017)
This study assumes that the urban organization is anchored in a body of social knowledge that dialogues with children who elaborate hypotheses about the city and its events, whether emblematic or not. The urban transformations promote a certain estrangement, affecting the meaning and the insertion of the children in the public space. This fact promotes the emergence of social representations. The World Cup 2014 in Cuiabá is taken as an emblematic context that favors the analysis of the forms of meaning of the city by children, in view of the urban transformations generated as a result of urban infrastructure projects announced as a legacy of the big event. This study aims to understand the social representations of children about Cuiabá before and after the World Cup 2014 in order to analyze the civic visibility of childhood in the context of the city, taking it as the main informant, active subject in the process of meaning of reality. As a theoretical contribution, the Theory of Social Representations (MOSCOVICI, 1978, 2013, JODELET, 2001, 2002) and the ontogenetic approach of the Social Representations (DUVEEN, 1995; CASTORINA, 2010) were used in dialogue with the Historical-Cultural Theory (VIGOTSKI , 2000, 200, 2009, 2010). Highlight the study on space and place (TUAN, 1983) and the contributions of the Sociology of Childhood (SARMENTO, 2007), as well as the discussions on the public spaces of Sennett (2014a, 2014b) and Jovchelovitch (2000). Has as object of this study 40 children from the Cuiabá public school, between nine and 12 years old, divided into four groups with 10 children each, distributed in three administrative regions of Cuiabá: East (1), West (2) And South (1). For data’s production, we used the semi-structured interview and the elaboration of cognitive maps by children. The following motes were used: a map about Cuiabá before the World Cup; Another map about Cuiabá after the World Cup. The data produced through the semi-structure interviews were processed with the help of lexical analysis - Alceste software and analyzed from the perspectives of Nucleus of Significance (AGUIAR, OZELLA, 2006) and the cognitive maps were submitted to Content Analysis (BARDIN, 1977 ). The data show that Cuiabá before and after the World Cup is represented, according to the children, from three images: the idyllic city, the city corrupted and the city possible. Children's experiences are guided by the most immediate family and community relations. The family dimension and the community dimension act in the mobility of the child in the city anchored in its cultural context. Note the tendency of the children to assume the configuration of the private space as reference for thinking the public space, being defined as free places. What is perceived is the need to feel included and to exercise their power of choice in relation to the occupation of the spaces of the city. The meanings presented by the children help to develop reflections about the relationship of children with the public spaces and provide clues for thinking about children's contexts in dialogue with the educational potential of the city, considering human development and social knowledge as historical, concomitant and dialogues.